OPTIMALISASI PELAKSANAAN PARA DASAR TARUNA KORPS MARINIR UNTUK MENCEGAH CIDERA SEHINGGA TERCAPAINYA ZERO ACCIDENT DALAM PENERJUNAN - Mayong Awang Edrik Putra; Wempi; Muh. Saichu (AKADEMI ANGKATAN LAUT, 2021)
The abilities given by the Marine Department to Marine Corps cadets are abilities thatare useful in later assignments. The ability is given in stages, one of which is ParaBasic. With the ability to jump in the Para Basic, it is hoped that Marine Corps cadetscan have more skills when they are assigned to carry troops. The existence of problemsthat occur both in the process of training and implementation, does not become abarrier in carrying out Para Basic. By being maximized in the training process, it willbetter prepare the parachutist in the jump. This research is a qualitative research withthe method used is the SWOT method. The current condition is described in detail anddata analysis is carried out using SWOT to bring up internal and external factors.Thisresearch can be used for planning and improvement of activities in the upcoming jump.Even the results can exceed the target and achieve zero accident during training,implementation and during assignments.